2011
DOI: 10.1007/s10900-011-9502-3
|View full text |Cite
|
Sign up to set email alerts
|

American Indian/Alaska Native Willingness to Provide Biological Samples for Research Purposes

Abstract: This article examines the willingness of American Indian/Alaska Natives (AI/AN) to provide biological samples for research purposes. Prior cases of abuse and misuse of individuals, materials, and data highlight ethical research concerns. Investigators may be hesitant to engage AI/ANs in research projects. We conducted a survey of AI/ANs in the central plains region of the US over 1 year. This convenience sample completed a series of questions on biological samples and research. Survey results (N = 998) indicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…In addition, Hughes et al [11] found that cultural beliefs hindered African American women from participating in genetic risk assessment studies, while Corbie-Smith et al [12] reported mistrust of the medical communities as a barrier for these populations to participate. Contrary to these studies, however, Filippi et al [13] and Wendler et al [14] found no statistical significant differences in willingness to participate in health research between different ethnic groups.…”
Section: Introductionmentioning
confidence: 91%
“…In addition, Hughes et al [11] found that cultural beliefs hindered African American women from participating in genetic risk assessment studies, while Corbie-Smith et al [12] reported mistrust of the medical communities as a barrier for these populations to participate. Contrary to these studies, however, Filippi et al [13] and Wendler et al [14] found no statistical significant differences in willingness to participate in health research between different ethnic groups.…”
Section: Introductionmentioning
confidence: 91%
“…Existing literature on the perspectives of Indigenous peoples in the U.S. and Canada indicates that the acceptability of research for these groups is contingent upon factors related to these components and principles of data management (James et al, 2014; Garrison et al, 2019). Issues of concern to Indigenous communities include: the types of data collected and how and from whom it is collected (Angal et al, 2016); the role of the community in the interpretation and analysis of data (Harding et al, 2012); the measures taken to maintain the security of data and the potential for loss of confidentiality (Sprague et al, 2013); the conditions under which biospecimens and other data types are stored (Hiratsuka et al, 2012a; Hiratsuka et al, 2012b; Haring et al, 2018); the terms of specimen withdrawal and disposal (Hiratsuka et al, 2012a; Hiratsuka et al, 2012b); with whom, for what purposes, and with whose permission data can be shared (Filippi et al, 2012); processes for returning results and progress reports to individuals participating in research (Hiratsuka et al, 2012a; Hiratsuka et al, 2012b); and, community involvement in the review and approval of dissemination products (Buchwald et al, 2006; Dirks et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Spero Manson and Candace Fleming from UCD. Although the purpose of the Forum was to obtain feedback about sharing health research results, a review of the literature and past research communication with community members suggested the inclusion of additional critical discussion topics, including research mistrust due to past unethical research practices and contemporary AN/AI community level research review practices (Bowekaty, 2002; Bromley, Mikesell, Jones, & Khodyakov, 2015; Filippi et al, 2012; Gottlieb, 2013; Guillemin et al, 2016; Hiratsuka, Brown, Hoeft, & Dillard, 2012). To address the issue of research mistrust in AN/AI communities and to foster open, reflective discussion, an important starting point for the Forum was to acknowledge the history of unethical and harmful research in the AN/AI community.…”
Section: Introductionmentioning
confidence: 99%